Nutrition and Bone Health 2014
DOI: 10.1007/978-1-4939-2001-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Bone Physiology: Bone Cells, Modeling, and Remodeling

Abstract: Key Points• The skeleton undergoes constant change through the processes of modeling and remodeling.• Modeling is defi ned as change in the size or shape of skeletal elements that occurs when formation and resorption are independent e.g., during growth or in an adaptive response to a change in mechanical loading.• Remodeling is defi ned as resorption and formation that occur essentially at the same site and in a programmed manner in which formation is temporally and spatially coupled to resorption. • Modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 136 publications
0
12
0
Order By: Relevance
“…In contrast, bone remodeling occurs throughout life and is responsible for the removal of older bone and its replacement with new bone structure [ 8 , 33 , 34 ]. Bone remodeling involves a sequence of cellular activities that occur within a specialized multicellular unit [ 35 ]. The bone multicellular unit is predominantly comprised of osteoclasts, osteoblasts, and osteocytes [ 24 ].…”
Section: Bone Biology Modelling and Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, bone remodeling occurs throughout life and is responsible for the removal of older bone and its replacement with new bone structure [ 8 , 33 , 34 ]. Bone remodeling involves a sequence of cellular activities that occur within a specialized multicellular unit [ 35 ]. The bone multicellular unit is predominantly comprised of osteoclasts, osteoblasts, and osteocytes [ 24 ].…”
Section: Bone Biology Modelling and Remodelingmentioning
confidence: 99%
“…There are 3–4 million basic multicellular units (BMU) produced each year, and approximately one million among them actively participate in the bone remodeling process [ 36 ]. Bone remodeling has four major stages: activation, resorption, reversal, and formation [ 35 ]. In the first step, osteoblastic stromal cells or lining cells are activated via lining cell retraction and endosteal membrane digestion by collagenase.…”
Section: Bone Biology Modelling and Remodelingmentioning
confidence: 99%
“…Indeed, debate exists about the potential systemic impact on other areas of the skeleton when one bone/region is loaded (Cresswell, Goff, Nguyen, Lee, & Hernandez, ; Lieberman, ; Sample et al, ; Sugiyama, Price, & Lanyon, ; Wallace et al, ), and how bone remodeling changes in response to differences in age (Nikander et al, ; Pearson & Lieberman, ; Ruff et al, ), muscle (Robling, ) versus joint reaction loading (Judex & Carlson, ; Schipilow, Macdonald, Liphardt, Kan, & Boyd, ), force (Christen et al, ; Schulte et al, ), and even how these factors are balanced against the role of the bone in maintaining homeostasis (Currey, ; Dempster & Raisz, ). Beyond this, large scale genetic studies have identified independent loci for cortical and trabecular bone that are associated with higher risk of fracture (Paternoster et al, ; Yerges et al, ), which suggests certain fixed aspects to bone morphology that may be insensitive to loading.…”
Section: The Evolution Of Hand Preference and Handednessmentioning
confidence: 99%
“…Another aspect of our results shows the presence of natural protein growth factors [22] and prebiotic non-digestible oligosaccharide fibers [23] in the salmon bone calcium which could be responsible for increased absorption of calcium, in spite of lower levels of elemental calcium intake, as compared to calcium carbonate. In particular, other researchers [24] have shown that the presence of oligosaccharides in the diet can lead to enhanced calcium absorption, particularly when present as part of a functional food.…”
Section: Discussionmentioning
confidence: 74%